Announcements of ECB unconventional programs: Implications for the sovereign risk of Italy - Matteo Falagiarda; Stefan Reitz (Kiel Institute for the World Economy (IfW), 2013)
This paper studies the effects of ECB communications about unconventional monetary policy operations on the perceived sovereign risk of Italy over the last five years. More than fifty events concerning non-standard operations are identified and classified with respect to the specific ECB program. The empirical results are derived from both an event-study analysis and a GARCH framework, which uses Italian long-term bond futures to disentangle expected from unexpected policy actions. We find that the ECB announcements about unconventional monetary policies substantially reduced Italian long-term government bond yield spread relative to German counterparts. Particularly, among the different types of measures, news about the Securities Markets Programme and the Outright Monetary Transactions are found to be effective in affecting the perceived sovereign risk of Italy.
Keywords: E43; E52; E58; G01; G12; 330; central bank communications; unconventional monetary policy; European sovereign debt crisis; event-study; GARCH models